Enhanced Resistance of atbzip62 against Pseudomonas syringae pv. tomato Suggests Negative Regulation of Plant Basal Defense and Systemic Acquired Resistance by AtbZIP62 Transcription Factor - Rizwana Begum Syed Nabi (MDPI AG, 2021)
The intrinsic defense mechanisms of plants toward pathogenic bacteria have been widely investigated for years and are still at the center of interest in plant biosciences research. This study investigated the role of the AtbZIP62 gene encoding a transcription factor (TF) in the basal defense and systemic acquired resistance in Arabidopsis using the reverse genetics approach. To achieve that, the atbzip62 mutant line (lacking the AtbZIP62 gene) was challenged with Pseudomonas syringae pv. tomato (Pst DC3000) inoculated by infiltration into Arabidopsis leaves at the rosette stage. The results indicated that atbzip62 plants showed an enhanced resistance phenotype toward Pst DC3000 vir over time compared to Col-0 and the susceptible disease controls, atgsnor1-3 and atsid2. In addition, the transcript accumulation of pathogenesis-related genes, AtPR1 and AtPR2, increased significantly in atbzip62 over time (0–72 h post-inoculation, hpi) compared to that of atgsnor1-3 and atsid2 (susceptible lines), with AtPR1 prevailing over AtPR2. When coupled with the recorded pathogen growth (expressed as a colony-forming unit, CFU mL−1), the induction of PR genes, associated with the salicylic acid (SA) defense signaling, in part explained the observed enhanced resistance of atbzip62 mutant plants in response to Pst DC3000 vir. Furthermore, when Pst DC3000 avrB was inoculated, the expression of AtPR1 was upregulated in the systemic leaves of Col-0, while that of AtPR2 remained at a basal level in Col-0. Moreover, the expression of AtAZI (a systemic acquired resistance -related) gene was significantly upregulated at all time points (0–24 h post-inoculation, hpi) in atbzip62 compared to Col-0 and atgsnor1-3 and atsid2. Under the same conditions, AtG3DPH exhibited a high transcript accumulation level 48 hpi in the atbzip62 background. Therefore, all data put together suggest that AtPR1 and AtPR2 coupled with AtAZI and AtG3DPH, with AtAZI prevailing over AtG3DPH, would contribute to the recorded enhanced resistance phenotype of the atbzip62 mutant line against Pst DC3000. Thus, the AtbZIP62 TF is proposed as a negative regulator of basal defense and systemic acquired resistance in plants under Pst DC3000 infection.